Mapping Derivative Relationships from BIBFRAME 2.0 to RDA. Issue 7 (2nd October 2020) - Sfakakis, Michalis; Zapounidou, Sofia; Papatheodorou, Christos
Abstract: The mapping from BIBFRAME 2.0 to Resource Description and Access (RDA) is studied focusing on core entities, inherent relationships, and derivative relationships. The proposed mapping rules are evaluated with two gold datasets. Findings indicate that 1) core entities, inherent and derivative relationships may be mapped to RDA, 2) the use of the bf:hasExpression property may cluster bf:Works with the same ideational content and enable their mapping to RDA Works with their Expressions, and 3) cataloging policies have a significant impact on the interoperability between RDA and BIBFRAME datasets. This work complements the investigation of semantic interoperability between the two models previously presented in this journal.